2016
DOI: 10.5603/nmr.2016.0032
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected axillary lymph node metastasis of nasopharyngeal and cervical cancer on 18FDG PET/CT: a case report

Abstract: Axillary lymph node metastasis (ALNM) from cancer except breast cancer is rare. Whole body 18F-Fluorodeoxyglucose positron emission tomography/computed tomography (PET/CT) that simultaneously offers anatomic and metabolic information is widely used and has become an effective modality in many clinical fields, especially oncology, and also may detect an unexpected metastasis. We report two cases of ALMN of nasopharyngeal and cervical cancer that was detected on whole body PET/CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…The most common pattern of NPC recurrence was local (73.5%), followed by locoregional lymph nodes (21.7%) and distant metastasis [ 3 ]. Bone, lung, and liver are common sites of distant metastases, and supraclavicular nodes are the most advanced extent of locoregional spread reported [ 4 ]. A recent retrospective study involving 2,599 NPC patients found that 59% of recurrent NPC occurs within the first two years after completion of treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common pattern of NPC recurrence was local (73.5%), followed by locoregional lymph nodes (21.7%) and distant metastasis [ 3 ]. Bone, lung, and liver are common sites of distant metastases, and supraclavicular nodes are the most advanced extent of locoregional spread reported [ 4 ]. A recent retrospective study involving 2,599 NPC patients found that 59% of recurrent NPC occurs within the first two years after completion of treatment [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be pointed out that the primary sentinel lymph nodes for head and neck cancers are the cervical lymph nodes rather than axillary lymph nodes, as established by previous publications (reviewed in 50 ). However, while less typical, axillary lymph node metastasis has been observed in multiple occasions in patients with cancers of oral origin, [51][52][53][54] suggesting the potential draining from cancers of the head and neck to the axillary lymph nodes. Similarly, we have demonstrated that front leg vaccination generated a significantly stronger antigen-specific CD8+ T cells response in the axillary lymph nodes of na€ ıve mice as compared to that in the iliac and inguinal lymph nodes, which exerts potent antitumor effects against tumors located in the buccal area ( Figs.…”
Section: Discussionmentioning
confidence: 99%
“…Very little research on this topic is reported as case reports [22][23][24]. We conducted a small sample retrospective study analysis to explore this issue, with the main purpose of improving the prognosis of such patients, increasing tumor control rates, and reducing the occurrence of metastasis.…”
Section: Introductionmentioning
confidence: 99%